2015
DOI: 10.3390/rs71014079
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sunlight Conditions on the Consistency of Vegetation Indices in Croplands—Effective Usage of Vegetation Indices from Continuous Ground-Based Spectral Measurements

Abstract: A ground-based network of spectral observations is useful for ecosystem monitoring and validation of satellite data. However, these observations contain inherent uncertainties due to the change of sunlight conditions. This study investigated the impact of changing solar zenith angles and diffuse/direct light conditions on the consistency of vegetation indices (normalized difference vegetation index (NDVI) and green-red vegetation index (GRVI)) derived from ground-based spectral measurements in three different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 44 publications
4
33
0
Order By: Relevance
“…NDVI was lower in the flight nearest solar noon, which agrees with the trend observed by Brede et al in UAS surveys of a tropical rainforest ecosystem [30]. Ishihara et al found a similar effect, sometimes with a sharp drop at solar noon, in continuous ground-based measurements of three types of cropland in Japan [45]. On the other hand, Assmann et al found an increase in NDVI with solar elevation [13], suggesting that the NDVI response may be site-specific.…”
Section: Flight Planningsupporting
confidence: 87%
“…NDVI was lower in the flight nearest solar noon, which agrees with the trend observed by Brede et al in UAS surveys of a tropical rainforest ecosystem [30]. Ishihara et al found a similar effect, sometimes with a sharp drop at solar noon, in continuous ground-based measurements of three types of cropland in Japan [45]. On the other hand, Assmann et al found an increase in NDVI with solar elevation [13], suggesting that the NDVI response may be site-specific.…”
Section: Flight Planningsupporting
confidence: 87%
“…The leaf-level analysis concentrated on chemical signals and laid the foundation of water removal application for scaling up to the canopy level. To better understand the mechanism at canopy level, the strategy should be examined in detail by considering other external factors such as canopy structure [ 57 , 58 ], soil background [ 59 , 60 ], solar zenith angle [ 61 , 62 ], view zenith angle [ 7 , 43 ], and diffuse/direct light condition [ 63 ]. Finally, the signal to noise ratio should also be accounted for in case the nitrogen-related second overtones are suppressed by the spectral noise from instruments and atmospheric interference [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because the reflectance values of plants vary in response to environmental changes in sunshine irradiance, solar angle [19], soil background, and water glint [20,21], reducing sampling noise due to these environmental changes for UAV-based measurement is crucial for accurate and stable data acquisition. This is particularly so for long-term measurement during an entire crop-growing season.…”
Section: Introductionmentioning
confidence: 99%